A 30-Year-Old Man with HIV, Fever, and a Rash - Radhika Shah; Saami Khalifian; Lyn Duncan; Daniela Kroshinsky; Bonnie Mackool (MDPI AG, 2018)
Patients who present with papular rashes have a wide differential diagnosis particularly in the setting of immune compromise. A 30-year-old male diagnosed with HIV since 2009, never on antiretroviral therapy, with a nadir CD4 count of 333 cells/mm3 and a current viral load of 44,300 copies/mL, presented with a diffuse monomorphic papular eruption that began on his trunk and extremities and subsequently spread to the penis and scrotum, sparing the distal acral sites. A thorough infectious workup revealed a positive rapid plasma reagin (RPR) and varicella IgM and IgG antibodies. Interestingly, the patient had been diagnosed and treated for syphilis in the past with a recent downtrending RPR drawn prior to hospitalization. Repeat RPR was elevated and a preliminary histopathology report demonstrated folliculocentric inflammation with lymphocytes, plasma cells, and polymorphonuclear leukocyte predominance supported the diagnosis of syphilis. After receiving intramuscular penicillin G benzathine, he developed intermittent fevers and new papules. Intravenous (IV) acyclovir was initiated for presumed disseminated varicella given his positive varicella-zoster virus IgM and IgG. However, final pathology results revealed a large spirochete burden. The fevers and rash progression were attributed to the development of a Jarisch-Herxheimer reaction. IV acyclovir was discontinued and he completed a course of intramuscular penicillin G benzathine. He was also given a course of doxycycline for rectal chlamydia which was diagnosed during hospitalization.